Private guns, public health - Hemenway, David, 1945- (University of Michigan Press, 2017)
"On an average day in the United States, guns are used to kill over ninety people and wound about three hundred more; yet such facts are accepted as a natural consequence of supposedly high American rates of violence. Private Guns, Public Health reveals the advantages of treating gun violence as a consumer safety and public health problem--an approach that emphasizes prevention over punishment and that has successfully reduced the rates of injury and death from infectious disease, car accidents, and tobacco consumption. Hemenway fair-mindedly and authoritatively outlines a policy course that would significantly reduce gun-related injury and death, pointing us toward a solution"--Publisher's description
Keywords: Gunshot wounds -- United States -- Prevention.; Firearms -- Law and legislation -- United States.; Gun control -- United States.; Medical policy -- United States.; Firearms ownership -- United States.; Firearms -- legislation & jurisprudence; Armes à feu -- Contrôle -- États-Unis.; Politique sanitaire -- États-Unis.; Armes à feu -- Possession -- États-Unis.; MEDICAL -- Surgery -- General.; Firearms -- Law and legislation; Firearms ownership; Gun control; Medical policy; United States